Impact of Visual Color and Texture on Infant Well-being and Development : A Case Study of Interior Design of Care Centers - Falusi, Tolulope; Omale, Reuben Peters (Aksen : Journal of Design and Creative Industry, 2025)
Psychologically, various emotions or responses can be evoked by certain colors and textures, the same in architecture. A baby's visual development can be significantly influenced by color and texture. It may also affect the child's emotional development, linguistic abilities and intellectual capabilities as they grow. This study examined the connection between global health and well-being and the interior design of childcare facilities, using the ABUAD multisystem childcare facilities and Telnet International School's childcare facilities as case studies. Census was employed to obtain the staff and parents' population at the care centers with a total number of 39 while the children at both care centers was 33. The study which employed a mixed-method approach relied on primary data (questionnaire) and unstructured interviews, alongside keen observation, amongst others. Staff and Parents were interviewed to gather data on the overall satisfaction and perceived impact of the interior design on the well-being of the children and staff. The findings suggest that incorporating vibrant and stimulating colors combined with soft textures in childcare facilities can positively impact a child's overall development, fostering creativity, cognitive skills, and emotional well-being. Furthermore, it highlights the importance of considering the psychological effects of color and texture in architectural design to create nurturing environments for children. Therefore, designers are advised to evaluate the safety and functionality of day-care centers, ensuring that it is easy to navigate and provide ample opportunities for exploration and play.